Ischemic neuropathy related to abdominal liposuction - Hernández, Germán Alberto; Fundación Oftalmológica de Santander (Pontificia Universidad Javeriana, 2010)
We describe a case of abdominal liposuction with unilateral visual loss post surgery, without simtoms. The Angiogram image diagnostic confirm optic ischemic neuropathy.The review include characteristics and treatment of this unfrecuent pathology. Ischemic neuropathy is not a rare disease, and association with esthetic procedures is important.